Differentiated Learning Model Based on the Cambridge Curriculum: A Case Study of Self Regulated Learning Ability and Mathematics Learning Achievement - Nadya Amalia; Ismaini Sitompul; Muhammad Khaedir Lutfi; Ima Hilmiatur Rosidah (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to analyze the implementation of a differentiated learning model based on the Cambridge Curriculum and its impact on students’ Self-Regulated Learning (SRL) skills and mathematics learning achievement. The research employed a mixed-methods approach with an embedded experimental design, in which quantitative and qualitative data were collected simultaneously to obtain a comprehensive understanding of the model’s effectiveness. The research subjects were Cambridge Lower Secondary students at a private school in Indonesia that implements the Cambridge Curriculum. The instruments used included a mathematics achievement test, an SRL questionnaire, and an observation checklist of learning activities. The results indicate that the implementation of differentiated learning significantly improved students’ learning outcomes compared to conventional instruction, particularly in problem-solving skills and understanding of basic mathematical concepts. In addition, there was an improvement in students’ self-regulation abilities, including goal setting, selection of learning strategies, and self-reflection. It can be concluded that the integration of differentiated learning with the Cambridge Curriculum is effective in enhancing student engagement, learner autonomy, and academic achievement in mathematics learning.